Demonstration of a low-complexity indoor visible light positioning system using an enhanced TDOA scheme - Du, Pengfei (2019)
In this paper, a low-complexity time-difference-of-arrival (TDOA) based indoor visible light positioning (VLP) system using an enhanced practical localization scheme based on cross correlation is proposed and experimentally demonstrated. The proposed TDOA scheme offers two advantages: 1) the use of virtual local oscillator to replace the real local oscillator for cross correlation at the receiver side so as to reduce the hardware complexity; 2) the application of cubic spline interpolation on the correlation function to reduce the rigorous requirement on the sampling rate and to enhance the time-resolution of cross correlation. In order to achieve the high positioning accuracy with minimum implementation complexity, parameter optimization is first performed in terms of sampling rate, interpolation factor, and data length for correlation. Using the obtained optimal parameters, we demonstrate a lowcomplexity indoor two-dimensional VLP system using the correlation-based TDOA scheme in a coverage area of 1.2 × 1.2 m 2 with a height of 2 m. The experimental results validate the feasibility of the proposed TDOA scheme, and an average positioning accuracy of 9.2 cm is achieved with a sampling rate of 500 MSa/s, an interpolation factor of 100 and a data length of 250 k samples.